Analisis Pengaruh Branding Terhadap Minat Beli Sepatu Lokal di Kalangan Gen Z: Studi di Desa Padenganploso - Tama, Taruna Firlian; Pratama, Adhitya Nugraha (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of branding on the purchase intention of local shoes among Generation Z, with a focus on Padenganploso Village. Branding is considered a strategic factor that can shape consumer perceptions and loyalty, especially among the younger generation, who are highly responsive to visual narratives and social values. This research employs a quantitative approach using a survey method and involves 250 respondents aged 15–25 years. The data collection instrument is a questionnaire using a Likert scale, covering 10 branding indicators and 6 purchase intention indicators. Data analysis is conducted using simple linear regression. The results show that branding has a positive and significant effect on purchase intention with an R² value of 0.417. These findings emphasize that strengthening an authentic branding strategy aligned with Gen Z values can boost purchasing power for local products. This study provides important implications for MSMEs and marketers designing youth-based local marketing strategies.